H 8 scheduling control on stochastic neutral systems subject to actuator nonlinearity - Yin, YanYan; Shi, P.; Liu, F.; Song, Y. (Taylor and Francis, 2013)
In this article, we propose a method for designing continuous gain-scheduled robust H 8 controller for a class of stochastic time-varying neutral systems subject to time-varying delay and actuator saturation. Initially, at different selected time points, one can obtain a series of time-constant neutral system models with Markov jumping parameter. Subsequently, H 8 controller is designed for each constant stochastic neutral system which guarantees exponential stochastic stabilisation of the system. Lastly, continuous gain-scheduled controller design method is employed, and an entire time-varying controller is designed for the whole working region. Simulation example is given to illustrate the effectiveness of developed techniques. © 2013 Taylor and Francis Group, LLC.